Effect of UV light on aqueous solution of bisglycinatonickel (II) dihydrate - Tiwari, V.K. (1985)
No chemical transformation was observed in the aqueous solution of bis-glycinatonickel (II) dihydrate even during 4-hour exposure to UV light. But when this exposure was carried out in the presence of Ti02, Zr02,Mg0,U203 and Fe203, within an hour interesting changes were observed includign the photodecomposition of the complex. Maximum photodecomposition was observed in the presence of U203. Alanine, aspartic acid, leucine and serine together with some unidentified products were formed. A remarkable change in the absorption spectra of the irradiated solution was observed.
Includes bibliographical references (pages 136-137) and index.
Keywords: Chemistry; Photodecomposition -- Bis-glycinatonickel (II) dihydrate